Interleukin 10 and dendritic cells are the main suppression mediators of regulatory T cells in human neurocysticercosis. (11th November 2015) - Arce-Sillas, A; Álvarez-Luquín, D D; Cárdenas, G; Casanova-Hernández, D; Fragoso, G; Hernández, M; Proaño Narváez, J V; García-Vázquez, F; Fleury, A; Sciutto, E; Adalid-Peralta, L
Summary: Neurocysticercosis is caused by the establishment of Taenia solium cysticerci in the central nervous system. It is considered that, during co-evolution, the parasite developed strategies to modulate the host's immune response. The action mechanisms of regulatory T cells in controlling the immune response in neurocysticercosis are studied in this work. Higher blood levels of regulatory T cells with CD4 + CD45RO + forkhead box protein 3 (FoxP3) high and CD4 + CD25 high FoxP3 + CD95 high phenotype and of non-regulatory CD4 + CD45RO + FoxP3 med T cells were found in neurocysticercosis patients with respect to controls. Interestingly, regulatory T cells express higher levels of cytotoxic T lymphocyte antigen 4 (CTLA-4), lymphocyte-activation gene 3 (LAG-3), programmed death 1 (PD-1) and glucocorticoid-induced tumour necrosis factor receptor (GITR), suggesting a cell-to-cell contact mechanism with dendritic cells. Furthermore, higher IL-10 and regulatory T cell type 1 (Tr1) levels were found in neurocysticercosis patients' peripheral blood, suggesting that the action mechanism of regulatory T cells involves the release of immunomodulatory cytokines. No evidence was found of the regulatory T cell role in inhibiting the proliferative response. Suppressive regulatory T cells from neurocysticercosis patients correlated negatively with late activated lymphocytes (CD4 + CD38 + ). Our results suggest that, during neurocysticercosis, regulatory T cells could control the immune response, probably by a cell-to-cell contact with dendritic cells and interleukin (IL)-10 release by Tr1, to create an immunomodulatory environment that may favour the development of T. solium cysticerci and their permanence in the central nervous system.